Function and Meaning of Penebel Society’s Prohibition - Ida Bagus Cahya Ambara; I Nyoman Kardana (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This research is of two objectives, which are to examine the functions of Penebel Community’s expressions of prohibition and to reveal the meanings of the expressions. This research was conducted using qualitative research design. Data were collected by visiting the farmers’ habitats, observing their activities while recording using voice memo app in gadget, and conducting interviews to confirm the researchers’ understanding of the recorded messages. Results showed that the functions of Penebel inhabitants’ expressions of prohibition are informational and directives. Meanwhile the meanings of the expressions are both explicit and implied. The explicit meaning refers to the lexical meanings of the words that form it, which can be seen in the dictionary. The implied meaning is found based on the context of its use. Instead of containing illogical meanings and are considered to be out of date with the times, these phrases of prohibition needs to be preserved by providing their comprehensible meanings to the younger generation for they are a part of living culture and language.